What is missing to understand sustainability? - Rosalba Thomas (Journal of Sustainability Perspectives, 2023)
Despite the enormous global problems linked not only to the ecological sphere, but also to the environmental, political, economic, social and cultural dimensions, humanity continues to consider that the discourse of sustainability has a close and unique relationship with nature. It is not like this. This text aims to make a deeper reflection on the historical context, interests and power relations that derive from considering sustainability as an alternative development model. More than a neutral discourse, sustainability must always land in a specific historical and spatial context, which allows it to adapt, and then perhaps become more operational and functional. The hypothesis places the media as simplistic and, at times partial interlocutors; but definitely not neutral, which prevents the individual from understanding the complex dynamics of the planet and the possible solutions to current problems. It is not only the fact that the media define what sustainability is, it is also important to reflect on how and why they do it.